Comparison of optically‐derived biomarkers in healthy and brain tumor tissue under one‐ and two‐photon excitation. Issue 11 (23rd July 2019) - Sibai, Mira; Mehidine, Hussein; Moawad, Emile Kaadou; Juchaux, Marjorie; Varlet, Pascale; Devaux, Bertrand; Abi Haidar, Darine
Abstract: The surgical outcome of brain tumor resection and needle biopsy is significantly correlated to the patient's prognosis. Brain tumor surgery is limited to resecting the solid portion of the tumor as current intraoperative imaging modalities are incapable of delineating infiltrative regions. For accurate delineation, in situ tissue interrogation at the submicron scale is warranted. Additionally, multimodal detection is required to remediate the genetically and molecularly heterogeneous nature of brain tumors, notably, that of gliomas, meningioma and brain metastasis. Multimodal detection, such as spectrally‐ and temporally‐resolved fluorescence under one‐ and two‐photon excitation, enables characterizing tissue based on several endogenous optical contrasts. In order to assign the optically‐derived parameters to different tissue types, construction of an optical database obtained from biopsied tissue is warranted. This report showcases the different quantitative and semi‐quantitative optical markers that may comprise the tissue discrimination database. These include: the optical index ratio, the optical redox ratio, the relative collagen density, spectrally‐resolved fluorescence lifetime parameters, two‐photon fluorescence imaging and second harmonic generation imaging. Abstract : Two photon fluorescence images (A‐C) and its corresponding histological images (D‐F) and the autofluorescence spectra under 405, 810 and 890 nm excitation (G‐I) of different human brain tissues, from three different types: control (A, D, G), low grade glioma tumor (B, E, H) and glioblastoma tumor (C, F, I).